Edukasi Penanganan Bantuan Hidup Dasar pada Kegawatdaruratan saat Tersedak dengan Teknik Back Blow di MAN 1 Banyumas - Icha Ervina Agustin; Made Suandika; Tin Utami (LPPM Akbid Harapan Ibu Pekalongan, 2025)
Choking is a medical emergency caused by a foreign object obstructing the airway, potentially leading to hypoxia or even death if not treated promptly. One recommended emergency intervention is the back blow technique, which involves applying forceful blows to the victim’s back to dislodge the obstruction. This community service activity aimed to increase public knowledge and skills in handling choking emergencies using the back blow technique. The method consisted of health education through lectures and live demonstrations, followed by pre- and post-tests to assess participants' knowledge and skills using structured questionnaires and skill checklists. The results indicated significant improvement. Prior to the intervention, 43% of participants had low knowledge and 33.3% had moderate knowledge. Post-intervention, all participants (100%) showed improved knowledge. In terms of skills, 73.3% were categorized as having low skills before training, while after demonstration, all participants (100%) reached a good skill level. The outputs of this program included an educational pocketbook and a journal publication.